Faktor-Faktor Yang Berhubungan Dengan Kejadian Hipertensi Pada Staf Sekretariat Majelis Ulama Indonesia Jakarta Pusat - Gusti Kumala Dewi; Mia Zulfiana (Jurnal Gizi dan Kuliner, 2022)
Hypertension is the silent killer in Indonesia. The study aimed to analyze the relationship between heredity factors, body mass index, and percent body fat with the incidence of hypertension at the secretariat staff of the Indonesian Ulema Council, Central Jakarta 2019. This research is an analytical descriptive cross-sectional study. Measuring blood pressure, body mass index, and percent body fat by filling out questionnaires related to heredity factors of hypertension were carried out to 42 Majelis Ulama Indonesia secretariat staff. The instruments used were a sphygmomanometer and stethoscope, Bioelectrical Impedance Analysis (BIA), microtoise, and questionnaires. The results showed that 31.0% of the study subjects suffered from hypertension. The bivariate variable test showed the results heredity factor (p 0.042 < 0.05), body mass index (p 0.031 < 0.05), and percent body fat (p 0.018 < 0.05). After the study, there is a significant relationship between all the variables studied. Keyword: Heredity, Body Mass Index, Hypertension